PENYELESAIAN SENGKETA KREDIT MACET PADA KREDIT TANPA AGUNAN BANK DIGITAL DI INDONESIA (Studi Pada Bank Digital LINE Bank) - Ruth Yohana Gebiola Manik (2023)
The presence of digital banks and the increase in lending in Indonesia, is the basis for research on credit granting and dispute resolution for Non-Performing Loan, considering that banks are tasked with channeling funds to the public through credit, of course, they must maintain public trust for the stability of the health of the bank itself. This research aims to find out the process of granting or applying for Non-Collateral Loan at Digital banks and to find out efforts to resolve Non-Performing Loan disputes on digital bank unsecured credit in Indonesia with a study of the Digital Bank "LINE Bank". This research uses normative juridical research with a statutory approach and conceptual approach, collecting data with interviews as a primary data source and literature review as a secondary data source which is analyzed using descriptive analysis. The results of the study concluded that lending without collateral at LINE Bank is applied with the principle of Knowing Your Customers (KYC) verification. The settlement of digital bank Non-Performing Loan disputes is resolved out of court through negotiations, credit restructuring, until the last resort is a lawsuit to the court. In terms of the application of prudential principles and the effectiveness of lending in digital banks, the use of Artificial Intelligence (AI) is worth considering.